Systemic risk in the financial sector: an analysis of the subprime-mortgage financial crisis - Martin Hellwig (Max Planck Institute for Research on Collective Goods, 2008)
The paper analyses the causes of the current crisis of the global financial system, with particular emphasis on the systemic elements that turned the crisis of subprime mortgage-backed securities in the United States, a small part of the overall system, into a worldwide crisis. The first half of the paper explains the role of mortgage securitization as a mechanism for allocating risks from real estate investments and discusses what has gone wrong and why in the implementation of this mechanism in the United States. The second half of the paper discusses the incidence of systemic risk in the crisis. Two elements of systemic risk are identified. First, there was excessive maturity transformation through conduits and structured-investment vehicles (SIVs); when this broke down in August 2007, the overhang of asset-backed securities that had been held by these vehicles put significant additional downward pressure on securities prices. Second, as the financial system adjusted to the recognition of delinquencies and defaults in US mortgages and to the breakdown of maturity transformation of conduits and SIVs, the interplay of market malfunctioning or even breakdown, fair value accounting and the insufficiency of equity capital at financial institutions, and, finally, systemic effects of prudential regulation created a detrimental downward spiral in the overall financial system. The paper argues that these developments have not only been caused by identifiably faulty decisions, but also by flaws in financial system architecture. In thinking about regulatory reform, one must therefore go beyond considerations of individual incentives and supervision and pay attention to issues of systemic interdependence and transparency.
Keywords: G01; G29; G32; 330; Mortgage Securitization; Subprime-Mortgage Financial Crisis; Systemic Risk; Banking Regulation; Capital Requirements; Wohnungsbaufinanzierung; Subprime-Hypothek; Securitization; Finanzmarktkrise; Systemrisiko; Kapitalmarktliberalisierung; Regulierung; Internationaler Finanzmarkt; Welt